Epigenetically regulated digital signaling defines epithelial innate immunity at the tissue level - Helen R. Clark (Nature Portfolio, 2021)
Fine tuning the immune response in line with the degree of threat is central to recognition of a pathogen versus commensal bacteria. Here the authors implicate a digital all-or-nothing cell response in control of the tissue level immune response.